Insights into the binding selectivity of harzianoic acids A and B to tetraspanin CD81 - Gérard Vergoten; Christian Bailly (Exploration of Drug Science)
Aim: Harzianoic acids A and B (Hz-A/B) are two rare cyclobutene-containing sesquiterpenes isolated from a marine strain of the sponge-associated fungus Trichoderma harzianum. They display anticancer and antiviral effects, reducing the entry of hepatitis C virus (HCV) into hepatocarcinoma cells. The large extracellular loop (LEL) of the tetraspanin protein CD81 represents a molecular target for both Hz-A and Hz-B. Methods: The interaction of Hz-A/B with CD81 has been modeled, using structures of the cholesterol-bound full-length protein and a truncated protein corresponding to the LEL portion. The models mimicked the closed and open conformations of the LEL. Results: The best ligand Hz-B can form stable complexes with the open LEL structure, whereas binding to the closed form is drastically reduced. Key H-bonds between the acid groups of Hz-B and the CD81-LEL domain stabilize the ligand-protein complex. A comparison of the interaction with the homologous tetraspanin CD9, which also presents a dynamic open/closed equilibrium, underlined the marked selectivity of Hz-A/B for CD81 over CD9. The cyclobutane-containing monoterpene grandisol, an insect pheromone, has been identified as a fragment that could be modulated to improve its modest interaction with CD81-LEL. Conclusions: The modeling docking analysis suggests that Hz-B is a robust CD81 binder, better interacting with the LEL portion of CD81 compared to CD9-LEL. The docking study paves the way to the design of small molecules targeting CD81. The study has implications for a better understanding of CD81 binding properties and the regulation of its activities.